Toxoplasma gondii Elongation Factor 1-Alpha (TgEF-1α) Is a Novel Vaccine Candidate Antigen against Toxoplasmosis - Wang, Shuai; Zhang, Zhenchao; Wang, Yujian; Gadahi, Javaid A.; Xu, Lixin; Yan, Ruofeng; Song, Xiaokai; Li, Xiangrui (Frontiers in Microbiology, 2017)
Toxoplasma gondii (T. gondii) is an obligate intracellular parasite which can infect almost all warm-blood animals, leading to toxoplasmosis. Screening and discovery of an effective vaccine candidate or new drug target is crucial for the control of this disease. In this study, the recombinant T. gondii elongation factor 1-alpha (rTgEF-1α) was successfully expressed in in Escherichia coli. Passive immunization of mice with anti-rTgEF-1α polyclonal antibody following challenge with a lethal dose of tachyzoites significantly increased the survival time compared with PBS control group. The survival time of mice challenged with tachyzoites pretreated with anti-rTgEF-1α PcAb also was significantly increased. Invasion of tachyzoites into mouse macrophages was significantly inhibited in the anti-rTgEF-1α PcAb pretreated group. Mice vaccinated with rTgEF-1α induced a high level of specific anti-T. gondii antibodies and production of IFN-gamma, interleukin-4. The expression levels of MHC-I and MHC-II molecules as well as the percentages of CD4+ and CD8+ T cells in mice vaccinated with rTgEF-1α was significantly increased respectively (P < 0.05), compared with all the controls. Immunization with rTgEF-1α significantly (P < 0.05) prolonged survival time (14.53±1.72 days) after challenge infection with the virulent T. gondii RH strain. These results indicate that T. gondii EF-1α plays an essential role in mediating host cell invasion by the parasite and, as such, could be a candidate vaccine antigen against toxoplasmosis.